1966
DOI: 10.1111/j.1469-8986.1966.tb02681.x
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Note on Eye Movement Patterns During Rem and Non Rem Sleep in Subjects With Congenital Nystagmus

Abstract: Fully developed nystagmus present in five Ss with congenital nystagmus while awake with eyes open or closed did not appear during the REM or non‐REM sleep phases. However, rapid conjugate eye movements were present during REM sleep in all five Ss, and could not be distinguished from the patterns recognized in normal subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1967
1967
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…b) The subjective estimation of the length of the dream correlates with the length of the REM period. (6). Both of these findings militate against a scanning hypothesis necessary for a psychic causation.…”
Section: Mental Activity During Sleepmentioning
confidence: 84%
“…b) The subjective estimation of the length of the dream correlates with the length of the REM period. (6). Both of these findings militate against a scanning hypothesis necessary for a psychic causation.…”
Section: Mental Activity During Sleepmentioning
confidence: 84%
“…In a study of endogenously induced nystagmus during sleep, Arkin, Weitzman, and Hastey (1966) reported that all night recordings of five subjects with congenital nystagmus manifesting clear-cut nystagmus during wakefulness nevertheless revealed no evidence of a nystagmic response during any of the sleep stages. In a subsequent replication of that study Arkin, Lutzky, and Toth (1972) confirmed their previous results.…”
mentioning
confidence: 99%